2010
DOI: 10.1061/(asce)wr.1943-5452.0000045
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Conjunctive Use Operations and Farm Decisions with Two-Stage Stochastic Quadratic Programming

Abstract: This paper applies two-stage stochastic quadratic programming to optimize conjunctive use operations of groundwater pumping and artificial recharge with farmer's expected revenue and cropping decisions. The two-stage programming approach allows modeling of water and permanent crop production decisions, with recourse for uncertain conditions of hydrology, annual crops, and irrigation technology decisions. Results indicate potential gains in expected net benefits and reduction in income variability from conjunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…Conjunctive use improves the water use efficiency and regional environment of irrigated areas by improving the availability and reliability of water (Cosgrove and Johnson, 2005;Cheng et al, 2009;Liu et al, 2013). The major benefits of conjunctive water use are the economic advantage and reduction of the adverse environmental impact by minimizing the crop stress during the critical growth stages (Marques et al, 2010). The conjunctive use of different quality water for irrigation improves the overall crop production and helps in achieving the food security.…”
Section: Introductionmentioning
confidence: 99%
“…Conjunctive use improves the water use efficiency and regional environment of irrigated areas by improving the availability and reliability of water (Cosgrove and Johnson, 2005;Cheng et al, 2009;Liu et al, 2013). The major benefits of conjunctive water use are the economic advantage and reduction of the adverse environmental impact by minimizing the crop stress during the critical growth stages (Marques et al, 2010). The conjunctive use of different quality water for irrigation improves the overall crop production and helps in achieving the food security.…”
Section: Introductionmentioning
confidence: 99%
“…The model application in Marques et al (2010) indicated that groundwater availability, price, and conjunctive use operations affect crop and irrigation technology decisions. Groundwater provides a stabilizing effect, increasing permanent (more valuable) crop acreage and expanding annual crops in dry years.…”
Section: Cu Operations and Irrigated Agriculture Decisions In Californiamentioning
confidence: 99%
“…In this context, the hydroeconomic model presented in Marques et al (2010) addresses farm decisions of water use and crop production. Surface and groundwater are conjunctively managed through artificial recharge to store surface water in the aquifer, and groundwater pumping to retrieve it.…”
Section: Cu Operations and Irrigated Agriculture Decisions In Californiamentioning
confidence: 99%
“…Bazargan-Lari et al (2009) developed a conflict resolution methodology for conjunctive use of water resources by first generating trade-off curves using a multi-objective genetic algorithm, and then selecting the best non-dominated solution using the Young conflict resolution theory (Young, 1993). Marques et al (2010) applied a two-stage quadratic programming model to maximize economic benefits of conjunctive use from crops, irrigation technology, the areas under permanent and annual crops, and surface water supply. They assumed groundwater withdrawal is constrained by artificial recharge of the aquifer, while also limiting the surface water supply in each year to a "sustainable" annual amount.…”
Section: Introductionmentioning
confidence: 99%